Differential effects of intermittent energy restriction vs. continuous energy restriction combined high-intensity interval training on overweight/obese adults: A randomized controlled trial - Xu, Rui; Cao, You-Xiang; Chen, Yu-Ting; Jia, Yu-Qi (Frontiers in Nutrition, 2022)
Background Intermittent energy restriction (IER) and continuous energy restriction (CER) are increasingly popular dietary approaches used for weight loss and overall health. These energy restriction protocols combined with exercise on weight loss and other health outcomes could achieve additional effects in a short-term intervention. Objectives To evaluate the effects of a 4-week IER or CER program on weight, blood lipids, and CRF in overweight/obese adults when combined with high-intensity interval training (HIIT). Methods Forty-eight overweight/obese adults [age: 21.3 ± 2.24 years, body mass index (BMI): 25.86 ± 2.64 kg⋅m–2] were randomly assigned to iER, cER, and normal diet (ND) groups (n = 16 per group), each consisting of a 4-week intervention. All of the groups completed HIIT intervention (3 min at 80% of V̇O2max followed by 3 min at 50% of V̇O2max), 30 min/training sessions, five sessions per week. iER subjects consumed 30% of energy needs on 2 non-consecutive days/week, and 100% of energy needs on another 5 days; cER subjects consumed 70% of energy needs; and ND subjects consumed 100% of energy needs. Body composition, waist circumference (WC) and hip circumference (HC), triglyceride (TG), total cholesterol (TC), low-density lipoprotein-cholesterol (LDL-c), high-density lipoprotein-cholesterol (HDL-c), and cardiorespiratory fitness (CRF) were measured before and after the intervention. Results Of the total 57 participants who underwent randomization, 48 (84.2%) completed the 4-week intervention. After intervention body composition and body circumference decreased in three groups, but no significant differences between groups. The iER tends to be superior to cER in the reduction of body composition and body circumference. The mean body weight loss was 4.57 kg (95% confidence interval [CI], 4.1–5.0, p < 0.001) in iER and 2.46 kg (95% CI, 4.1–5.0, p < 0.001) in iER. The analyses of BMI, BF%, WC, and HC were consistent with the primary outcome results. In addition, TG, TC, HDL-c, and CRF improved after intervention but without significant changes (p > 0.05). Conclusion Both IER and CER could be effective in weight loss and increased CRF when combined with HIIT. However, iER showed greater benefits for body weight, BF%, WC, and HC compared with cER.